1986
DOI: 10.1007/bf02311135
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of waterborne selenium by rainbow trout (Salmo gairdneri), eggs, fry and juveniles

Abstract: The effect of waterborne selenite levels on selenium accumulated by different developmental stages of rainbow trout (Salmo gairdneri) was studied using(75)SeO 3 (=) as a tracer. All stages readily accumulated selenium at both high and low concentrations, but the rate of accumulation increased as the trout developed from the egg to the juvenile feeding stage. The low rate of selenium accumulation by embryos seemed to be related more to a lack of gills than to the presence of a chorion. The bioconcentration fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The waterborne Se content of 2·2 μg/l determined at the beginning of the present study according to Darrouzès et al ( 46 , 47 ) was within the range that rarely produced discernible adverse effects on fish according to Hamilton ( 45 ) . This level was also unlikely to contribute significantly to the dietary requirement for Se even if waterborne Se has been shown to be readily accumulated by rainbow trout ( 48 ) . The lowest whole-body Se content was found in fish fed the non-supplemented plant-based diet PSe0.…”
Section: Discussionmentioning
confidence: 99%
“…The waterborne Se content of 2·2 μg/l determined at the beginning of the present study according to Darrouzès et al ( 46 , 47 ) was within the range that rarely produced discernible adverse effects on fish according to Hamilton ( 45 ) . This level was also unlikely to contribute significantly to the dietary requirement for Se even if waterborne Se has been shown to be readily accumulated by rainbow trout ( 48 ) . The lowest whole-body Se content was found in fish fed the non-supplemented plant-based diet PSe0.…”
Section: Discussionmentioning
confidence: 99%
“…This particular behaviour indicates that the environment has become unsuitable for the fish to survive. Fish may take up selenium through their gills, as selenium accumulation in rainbow trout is greater after gill development (Hodson et al, 1986). Gill lamellae which are normally thin and delicate are necessary for gas exchange in respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Hodson et al [9] made an experiment in which rainbow trout eggs were exposed to waterborne selenium. They found that most of the accumulated selenium was in the eggshell (i.e., chorion) of the developing eggs and less than 25% in the embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have shown the accumulation of waterborne chemicals in eggs, the distribution of chemicals in different tissues of the egg is poorly known. A study with rainbow trout eggs exposed to radiolabeled selenium suggested that selenium accumulation is not necessarily the same in different parts of the egg, and that the relative distribution between the eggshell and the inner parts of the egg depend on the exposure concentration [9]. Similarly, the distribution of waterborne tetrachlorobiphenyl in lake trout eggs was reported to differ in different parts of the egg, with the total amount of accumulated chemical increasing in the inner parts of the egg but remaining relatively constant in the eggshell during the 4‐h exposure study [10].…”
Section: Introductionmentioning
confidence: 99%